I'd rather be home - Vanden Bosch, James; Terra Nova Films (Chicago, Ill. : Terra Nova Films, 1997)
(Producer) This video follows, over a period of seven years, the case of Norman, an older man repeatedly abused by one of his adult sons. The son lives at home (along with Norman wife and other adult son). Since Norman is unwilling to take legal action, the situation remains unresolved for years with Norman leaving home for short periods of time, then returning, hoping his son will change. Eventually, after a severe beating, Norman ends up in a nursing home, has a mild stroke, and is placed under state guardianship.
Videocassette is available at Koleksi Media, PHUKM
Produced and directed by James Vanden Bosch
Keywords: Elder Abuse; Domestic Violence; Family relations